Evaluating the effect of stone bunds erosion control on vegetation trend in South-West Burkina Faso - A fine scale remote sensing perspective in the Ioba Province - Asare, Yaw Mensah (2019)
A thesis submitted to the Department of Civil Engineering, College of Engineering, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirement for the degree of Doctor of philosophy in Climate Change and Land Use.